Method for preparing magnetic corrosion-resistant ceramic coating on surface of titanium alloy
The preparation of magnetic ceramic coatings on the surface of titanium alloys through microarc oxidation and segmented oxidation technology has solved the problem of non-magnetic restriction application of ceramic coatings in the prior art, significantly improved the corrosion resistance and magnetic properties of titanium alloys, and extended the service life And broadened the application areas.
Patent Information
- Application Number
- CN202410220696.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2024-12-13
AI Technical Summary
The ceramic coating prepared by the existing microarc oxidation technology on the surface of titanium alloy is non-magnetic, limiting the application of titanium alloys in clinical medicine, information storage and sensing.
Microarc oxidation segmented oxidation technology is used to prepare magnetic ceramic coatings on the surface of titanium alloy. By increasing the iron content in the coating under high voltage and high current conditions, the corrosion resistance and magnetic properties of the magnetic coating are significantly improved, combined with iron oxalate The precursor solution and specific electrolyte are processed to form a dense and uniform magnetic coating.
The corrosion resistance and magnetic properties of titanium alloy are significantly improved, the bonding strength between the coating and the substrate is improved, micropores and volcanic protrusions exist on the surface of the ceramic coating, the corrosion resistance current density is reduced, and the ferromagnetic properties of the magnetic ceramic coating are significant. The service life of the titanium alloy implant is extended.
Smart Images

Figure CN119121348A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceramic coating. Background Art
[0002] Titanium and titanium alloys are widely used in aerospace, automotive, artificial joints, bone trauma repair products, cardiovascular stents, dental implants and other fields due to their advantages such as high strength, low modulus, excellent corrosion resistance and good biocompatibility. In long-term clinical applications, titanium and its alloys have also exposed some inherent defects. As non-degradable materials, titanium-based implants face surface physiological corrosion during long-term service, and corrosion products can cause aseptic inflammation and infection. Therefore, improving the corrosion resistance of titanium alloy implant materials has important application value. In addition, studies have shown that titanium alloy magnetic coatings can improve the sensitivity and stability of hard disk drive read / write heads, thereby improving the performance and reliability of storage devices. It can also be used to manufacture magnetic sensors and magnetic sensors. Titanium alloy magnetic coatings are also used in the biomedical field. For example, magnetic coatings are prepared on the surface of orthopedic implants of titanium alloys to achieve precise positioning and manipulation. Soluble factors such as growth factors, hormones and peptides are directly delivered to the implant site, and have a significant effect on promoting osteoblast adhesion, proliferation and differentiation, significantly improving the stability of implant materials and host bones. However, titanium and titanium alloy materials have no magnetism. As common materials for biological implants, the preparation of magnetic corrosion-resistant ceramic coatings on the surface of titanium alloys can give titanium alloy implants magnetic properties, enhance the osteogenic induction activity of titanium alloy implants, increase the service life of titanium alloy implants, and further broaden the application field of titanium alloys. Therefore, constructing magnetic corrosion-resistant coatings on the surface of titanium alloy materials is of great significance for improving the clinical medicine, information storage and sensing of titanium implants. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that the ceramic coating prepared on the surface of titanium alloy by the existing micro-arc oxidation technology is non-magnetic, which limits the application of titanium alloy in clinical medicine, information storage and sensing and other fields, and to provide a method for preparing a magnetic corrosion-resistant ceramic coating on the surface of titanium alloy.
[0004] A method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface is specifically completed by the following steps:
[0005] 1. Titanium alloy pretreatment:
[0006] The titanium alloy is polished using sandpaper to obtain a titanium alloy with a bright surface;
[0007] 2. Ultrasonic oil removal:
[0008] The titanium alloy with a bright surface is immersed in a degreasing liquid, and then ultrasonically treated to obtain the titanium alloy after ultrasonic treatment; the titanium alloy is rinsed with distilled water, and then blown dry to obtain the degreasing titanium alloy;
[0009] 3. Preparation of ferric oxalate precursor solution:
[0010] The ferric oxalate, glycerol and deionized water are mixed, and ultrasonically treated for a period of time at room temperature to obtain a ferric oxalate precursor solution;
[0011] 4. Micro-arc oxidation I:
[0012] Firstly, micro-arc oxidation electrolyte I is added into a stainless steel cup, and then the degreased titanium alloy is immersed into the micro-arc oxidation electrolyte, and then the stainless steel cup is connected to the negative electrode of the micro-arc oxidation power supply, and the degreased titanium alloy is connected to the positive electrode of the micro-arc oxidation power supply, and the reaction is carried out for 120s to 180s under the conditions of a constant forward voltage of 400V to 450V, a negative voltage of 60V to 80V, a duty cycle of 20% to 40% and a frequency of 1000Hz to 2000Hz to obtain a titanium alloy treated by micro-arc oxidation I;
[0013] The micro-arc oxidation electrolyte I described in step 4 is composed of trisodium phosphate, disodium hydrogen phosphate, sodium fluoride and water, wherein the concentration of trisodium phosphate is 15g / L to 25g / L, the concentration of disodium hydrogen phosphate is 4g / L to 6g / L, and the concentration of sodium fluoride is 1g / L to 3g / L;
[0014] 5. Micro-arc oxidation II:
[0015] First, the graphite electrode and the titanium alloy treated by micro-arc oxidation I were immersed in the micro-arc oxidation electrolyte II, and then the graphite electrode was connected to the negative electrode of the micro-arc oxidation power supply, and the titanium alloy treated by micro-arc oxidation I was connected to the positive electrode of the micro-arc oxidation power supply. An N52 NdFeB magnet was placed in front and behind the exposed part of the titanium alloy. The current density was 12A / dm 2 ~20A / dm 2 , reacting for 30 min to 45 min under the conditions of a duty cycle of 10% to 20% and a frequency of 50 Hz to 200 Hz to obtain a titanium alloy magnetic ceramic coating;
[0016] The micro-arc oxidation electrolyte II described in step five is composed of trisodium phosphate, disodium hydrogen phosphate, sodium borate, sodium tungstate, potassium ferrocyanide, ferric oxalate precursor solution and water, wherein the concentration of trisodium phosphate is 10g / L~20g / L, the concentration of disodium hydrogen phosphate is 5g / L~15g / L, the concentration of sodium borate is 5g / L~9g / L, the concentration of sodium tungstate is 0.5g / L~1.5g / L, the concentration of potassium ferrocyanide is 3g / L~8g / L, and the concentration of ferric oxalate precursor solution is 150mL / L~250mL / L.
[0017] Advantages of the present invention:
[0018] 1. The present invention adopts micro-arc oxidation segmented oxidation to prepare titanium alloy magnetic ceramic coating. In the first stage of micro-arc oxidation, on the one hand, the bonding strength of the titanium alloy coating is improved, and on the other hand, the iron content in the coating is increased under high voltage and high current conditions, which significantly improves the corrosion resistance and magnetic properties of the magnetic coating; the bonding strength between the coating and the substrate is 50MPa, and after the titanium alloy surface is strengthened, a dense and uniform magnetic coating is obtained; there are a large number of micropores and volcano-like protrusions on the surface of the ceramic coating;
[0019] 2. The magnetic ceramic coating prepared by the present invention is mainly composed of substrate oxidized TiO2, containing a small amount of FePO4 phase. The ceramic coating generally also contains a large amount of amorphous iron-containing substances. After calcination at 700°C for 2h, it can be clearly seen that the content of FePO4 phase increases and γ-Fe2O3 phase appears, which further proves that the magnetic ceramic coating contains a large amount of Fe element;
[0020] 3. The magnetic ceramic coating prepared by the present invention has significant ferromagnetic properties;
[0021] 4. The corrosion resistance current density of the magnetic ceramic coating prepared by the present invention is reduced to 6.8×10 -8 A / cm 2 , the corrosion potential is 0.02V, while the corrosion current density of the base titanium alloy is 2.9×10 -6 A / cm 2 , corrosion potential -0.68V. The magnetic ceramic coating prepared by micro-arc oxidation segmented treatment in the present invention has a corrosion current density nearly 2 orders of magnitude lower than that of the titanium alloy substrate, and the potential is positively shifted by 0.70V, which significantly improves the corrosion resistance of the titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the titanium alloy magnetic ceramic coating prepared in Example 1;
[0023] Figure 2 The titanium alloy magnetic ceramic coating prepared in Example 1 and its XRD spectrum after calcination at 700°C for 2h;
[0024] Figure 3 MH curve of the titanium alloy magnetic ceramic coating prepared in Example 1;
[0025] Figure 4 The corrosion resistance of the titanium alloy substrate and the titanium alloy magnetic ceramic coating prepared in Example 1. DETAILED DESCRIPTION
[0026] Specific implementation method 1: This implementation method is a method for preparing a magnetic corrosion-resistant ceramic coating on the surface of a titanium alloy, which is specifically completed by the following steps:
[0027] 1. Titanium alloy pretreatment:
[0028] The titanium alloy is polished using sandpaper to obtain a titanium alloy with a bright surface;
[0029] 2. Ultrasonic oil removal:
[0030] The titanium alloy with a bright surface is immersed in a degreasing liquid, and then ultrasonically treated to obtain the titanium alloy after ultrasonic treatment; the titanium alloy is rinsed with distilled water, and then blown dry to obtain the degreasing titanium alloy;
[0031] 3. Preparation of ferric oxalate precursor solution:
[0032] The ferric oxalate, glycerol and deionized water are mixed, and ultrasonically treated for a period of time at room temperature to obtain a ferric oxalate precursor solution;
[0033] 4. Micro-arc oxidation I:
[0034] Firstly, micro-arc oxidation electrolyte I is added into a stainless steel cup, and then the degreased titanium alloy is immersed into the micro-arc oxidation electrolyte, and then the stainless steel cup is connected to the negative electrode of the micro-arc oxidation power supply, and the degreased titanium alloy is connected to the positive electrode of the micro-arc oxidation power supply, and the reaction is carried out for 120s to 180s under the conditions of a constant forward voltage of 400V to 450V, a negative voltage of 60V to 80V, a duty cycle of 20% to 40% and a frequency of 1000Hz to 2000Hz to obtain a titanium alloy treated by micro-arc oxidation I;
[0035] The micro-arc oxidation electrolyte I described in step 4 is composed of trisodium phosphate, disodium hydrogen phosphate, sodium fluoride and water, wherein the concentration of trisodium phosphate is 15g / L to 25g / L, the concentration of disodium hydrogen phosphate is 4g / L to 6g / L, and the concentration of sodium fluoride is 1g / L to 3g / L;
[0036] 5. Micro-arc oxidation II:
[0037] First, the graphite electrode and the titanium alloy treated by micro-arc oxidation I were immersed in the micro-arc oxidation electrolyte II, and then the graphite electrode was connected to the negative electrode of the micro-arc oxidation power supply, and the titanium alloy treated by micro-arc oxidation I was connected to the positive electrode of the micro-arc oxidation power supply. An N52 NdFeB magnet was placed in front and behind the exposed part of the titanium alloy. The current density was 12A / dm 2 ~20A / dm 2 , reacting for 30 min to 45 min under the conditions of a duty cycle of 10% to 20% and a frequency of 50 Hz to 200 Hz to obtain a titanium alloy magnetic ceramic coating;
[0038] The micro-arc oxidation electrolyte II described in step five is composed of trisodium phosphate, disodium hydrogen phosphate, sodium borate, sodium tungstate, potassium ferrocyanide, ferric oxalate precursor solution and water, wherein the concentration of trisodium phosphate is 10g / L~20g / L, the concentration of disodium hydrogen phosphate is 5g / L~15g / L, the concentration of sodium borate is 5g / L~9g / L, the concentration of sodium tungstate is 0.5g / L~1.5g / L, the concentration of potassium ferrocyanide is 3g / L~8g / L, and the concentration of ferric oxalate precursor solution is 150mL / L~250mL / L.
[0039] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the size of the titanium alloy in step 1 is 200 mm×20 mm×2 mm; in step 1, 120#, 180#, 600#, and 2000# SiC sandpaper are used to grind and polish the titanium alloy. The other steps are the same as those in specific implementation method 1.
[0040] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the degreasing liquid described in step 2 is composed of a surfactant, anhydrous ethanol, trisodium phosphate, disodium ethylenediaminetetraacetic acid and water, wherein the concentration of the surfactant is 15 g / L to 25 g / L, the concentration of anhydrous ethanol is 80 mL / L to 120 mL / L, the concentration of trisodium phosphate is 25 g / L to 35 g / L, and the concentration of disodium ethylenediaminetetraacetic acid is 1 g / L to 3 g / L. The other steps are the same as those of specific embodiment 1 or 2.
[0041] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the surfactant is AEO-9. The other steps are the same as those of specific embodiments 1 to 3.
[0042] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that: the temperature of the degreasing liquid in step 2 is 30°C to 40°C; the power of the ultrasonic treatment in step 2 is 100W, and the time of the ultrasonic treatment is 10min to 20min; in step 2, the titanium alloy is rinsed with distilled water for 3 to 5 times, and then dried with a hair dryer to obtain the degreasing titanium alloy. The other steps are the same as those in specific implementation methods 1 to 4.
[0043] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the mass volume ratio of ferric oxalate, glycerol and deionized water described in step 3 is (15g-25g): (80mL-120mL): (80mL-120mL); the power of the ultrasonic treatment described in step 3 is 100W, and the time of the ultrasonic treatment is 10min-20min. The other steps are the same as those of specific embodiments 1 to 5.
[0044] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the size of the N52 NdFeB magnet in step 5 is 40 mm×10 mm×5 mm. The other steps are the same as those in specific embodiments 1 to 6.
[0045] The following examples are used to verify the beneficial effects of the present invention:
[0046] Embodiment 1: A method for preparing a magnetic ceramic coating on a titanium alloy surface is specifically completed by the following steps:
[0047] 1. Titanium alloy pretreatment:
[0048] The titanium alloy was polished using 120#, 180#, 600#, and 2000# SiC sandpapers in sequence to obtain a titanium alloy with a bright surface;
[0049] The size of the titanium alloy described in step 1 is 200 mm×20 mm×2 mm;
[0050] 2. Ultrasonic oil removal:
[0051] The titanium alloy with a bright surface is immersed in a degreasing liquid at a temperature of 35°C, and then ultrasonically treated for 10 minutes at an ultrasonic power of 100W to obtain the titanium alloy after ultrasonic treatment; the titanium alloy is rinsed with distilled water for 3 times, and then dried with a hair dryer to obtain the titanium alloy after degreasing;
[0052] The degreasing liquid described in step 2 is composed of a surfactant, anhydrous ethanol, trisodium phosphate, disodium ethylenediaminetetraacetic acid and water, wherein the concentration of the surfactant is 20 g / L, the concentration of anhydrous ethanol is 100 mL / L, the concentration of trisodium phosphate is 30 g / L, and the concentration of disodium ethylenediaminetetraacetic acid is 2 g / L;
[0053] The surfactant described in step 2 is AEO-9;
[0054] 3. Preparation of ferric oxalate precursor solution:
[0055] 20 g of ferric oxalate, 100 mL of glycerol and 100 mL of deionized water were mixed, and ultrasonic treatment was performed at room temperature with an ultrasonic power of 100 W for 10 min to obtain a ferric oxalate precursor solution;
[0056] 4. Micro-arc oxidation I:
[0057] Firstly, micro-arc oxidation electrolyte I is added into a stainless steel cup, and then the degreased titanium alloy is immersed in the micro-arc oxidation electrolyte, and then the stainless steel cup is connected to the negative electrode of the micro-arc oxidation power supply, and the degreased titanium alloy is connected to the positive electrode of the micro-arc oxidation power supply, and the reaction is carried out for 120s under the conditions of a constant forward voltage of 400V, a negative voltage of 80V, a duty cycle of 30% and a frequency of 1000Hz to obtain a titanium alloy treated by micro-arc oxidation I;
[0058] The micro-arc oxidation electrolyte I described in step 4 is composed of trisodium phosphate, disodium hydrogen phosphate, sodium fluoride and water, wherein the concentration of trisodium phosphate is 20 g / L, the concentration of disodium hydrogen phosphate is 5 g / L, and the concentration of sodium fluoride is 2 g / L;
[0059] 5. Micro-arc oxidation II:
[0060] First, the graphite electrode and the titanium alloy treated by micro-arc oxidation I were immersed in the micro-arc oxidation electrolyte II, and then the graphite electrode was connected to the negative electrode of the micro-arc oxidation power supply, and the titanium alloy treated by micro-arc oxidation I was connected to the positive electrode of the micro-arc oxidation power supply. An N52 NdFeB magnet was placed in front and behind the exposed part of the titanium alloy. The current density was 12A / dm 2 , reacting for 30 minutes under the conditions of a duty cycle of 10% and a frequency of 50 Hz to obtain a titanium alloy magnetic ceramic coating;
[0061] The size of the N52 NdFeB magnet described in step 5 is 40mm×10mm×5mm;
[0062] The micro-arc oxidation electrolyte II described in step five is composed of trisodium phosphate, disodium hydrogen phosphate, sodium borate, sodium tungstate, potassium ferrocyanide, ferric oxalate precursor solution and water, wherein the concentration of trisodium phosphate is 15g / L, the concentration of disodium hydrogen phosphate is 10g / L, the concentration of sodium borate is 7g / L, the concentration of sodium tungstate is 1g / L, the concentration of potassium ferrocyanide is 5g / L, and the concentration of ferric oxalate precursor solution is 200mL / L.
[0063] Figure 1 This is a SEM image of the titanium alloy magnetic ceramic coating prepared in Example 1;
[0064] from Figure 1 It can be clearly observed that there are a large number of micropores and volcano-like protrusions on the surface of the ceramic coating.
[0065] Figure 2 The titanium alloy magnetic ceramic coating prepared in Example 1 and its XRD spectrum after calcination at 700°C for 2h;
[0066] from Figure 2It can be concluded that the coating is mainly composed of matrix oxidized TiO2 and contains a small amount of FePO4 phase. The ceramic coating generally also contains a large amount of amorphous iron-containing substances. After calcination at 700°C for 2h, it can be obviously seen that the FePO4 phase content increases and the γ-Fe2O3 phase appears, which further proves that the magnetic ceramic coating contains a large amount of Fe elements.
[0067] Figure 3 MH curve of the titanium alloy magnetic ceramic coating prepared in Example 1;
[0068] from Figure 3 It can be concluded that the prepared ceramic coating has significant ferromagnetic properties.
[0069] Figure 4 The corrosion resistance of the titanium alloy substrate and the titanium alloy magnetic ceramic coating prepared in Example 1.
[0070] from Figure 4 It can be seen that the corrosion current density of the magnetic ceramic coating is reduced to 6.8×10 -8 A / cm 2 , the corrosion potential is 0.02V, and the corrosion current density of the titanium alloy substrate is 2.9×10 -6 A / cm 2 , corrosion potential -0.68V; the magnetic ceramic coating prepared by micro-arc oxidation segmented treatment has a corrosion current density nearly 2 orders of magnitude lower than that of the titanium alloy substrate, and the potential is positively shifted by 0.70V, which significantly improves the corrosion resistance of the titanium alloy.
Claims
1. A method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface, characterized in that The method is specifically completed according to the following steps:
1. Titanium alloy pretreatment: The titanium alloy is polished using sandpaper to obtain a titanium alloy with a bright surface; 2. Ultrasonic oil removal: The titanium alloy with a bright surface is immersed in a degreasing liquid, and then ultrasonically treated to obtain the titanium alloy after ultrasonic treatment; the titanium alloy is rinsed with distilled water, and then blown dry to obtain the degreasing titanium alloy; 3. Preparation of ferric oxalate precursor solution: The ferric oxalate, glycerol and deionized water are mixed, and ultrasonically treated for a period of time at room temperature to obtain a ferric oxalate precursor solution; 4. Micro-arc oxidation I: Firstly, micro-arc oxidation electrolyte I is added into a stainless steel cup, and then the degreased titanium alloy is immersed into the micro-arc oxidation electrolyte, and then the stainless steel cup is connected to the negative electrode of the micro-arc oxidation power supply, and the degreased titanium alloy is connected to the positive electrode of the micro-arc oxidation power supply, and the reaction is carried out for 120s to 180s under the conditions of a constant forward voltage of 400V to 450V, a negative voltage of 60V to 80V, a duty cycle of 20% to 40% and a frequency of 1000Hz to 2000Hz to obtain a titanium alloy treated by micro-arc oxidation I; The micro-arc oxidation electrolyte I described in step 4 is composed of trisodium phosphate, disodium hydrogen phosphate, sodium fluoride and water, wherein the concentration of trisodium phosphate is 15g / L to 25g / L, the concentration of disodium hydrogen phosphate is 4g / L to 6g / L, and the concentration of sodium fluoride is 1g / L to 3g / L; 5. Micro-arc oxidation II: First, the graphite electrode and the titanium alloy treated by micro-arc oxidation I were immersed in the micro-arc oxidation electrolyte II, and then the graphite electrode was connected to the negative electrode of the micro-arc oxidation power supply, and the titanium alloy treated by micro-arc oxidation I was connected to the positive electrode of the micro-arc oxidation power supply. An N52 NdFeB magnet was placed in front and behind the exposed part of the titanium alloy. The current density was 12A / dm 2 ~20A / dm 2 , reacting for 30 min to 45 min under the conditions of a duty cycle of 10% to 20% and a frequency of 50 Hz to 200 Hz to obtain a titanium alloy magnetic ceramic coating; The micro-arc oxidation electrolyte II described in step five is composed of trisodium phosphate, disodium hydrogen phosphate, sodium borate, sodium tungstate, potassium ferrocyanide, ferric oxalate precursor solution and water, wherein the concentration of trisodium phosphate is 10g / L~20g / L, the concentration of disodium hydrogen phosphate is 5g / L~15g / L, the concentration of sodium borate is 5g / L~9g / L, the concentration of sodium tungstate is 0.5g / L~1.5g / L, the concentration of potassium ferrocyanide is 3g / L~8g / L, and the concentration of ferric oxalate precursor solution is 150mL / L~250mL / L.
2. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 1, characterized in that The size of the titanium alloy described in step one is 200mm×20mm×2mm; in step one, 120#, 180#, 600#, and 2000# SiC sandpapers are used in sequence to grind and polish the titanium alloy.
3. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 1, characterized in that The degreasing liquid described in step 2 is composed of a surfactant, anhydrous ethanol, trisodium phosphate, disodium ethylenediaminetetraacetic acid and water, wherein the concentration of the surfactant is 15g / L to 25g / L, the concentration of anhydrous ethanol is 80mL / L to 120mL / L, the concentration of trisodium phosphate is 25g / L to 35g / L, and the concentration of disodium ethylenediaminetetraacetic acid is 1g / L to 3g / L.
4. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 3, characterized in that The surfactant is AEO-9.
5. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 1, characterized in that The temperature of the degreasing liquid described in step 2 is 30°C to 40°C; the power of the ultrasonic treatment described in step 2 is 100W, and the time of the ultrasonic treatment is 10min to 20min; in step 2, the titanium alloy is rinsed 3 to 5 times with distilled water, and then dried with a hair dryer to obtain the degreased titanium alloy.
6. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 1, characterized in that The mass volume ratio of ferric oxalate, propylene glycol and deionized water described in step three is (15g~25g):(80mL~120mL):(80mL~120mL); the power of the ultrasonic treatment described in step three is 100W, and the time of ultrasonic treatment is 10min~20min.
7. The method for preparing a magnetic corrosion-resistant ceramic coating on a titanium alloy surface according to claim 1, characterized in that The size of the N52 NdFeB magnet described in step 5 is 40 mm×10 mm×5 mm.
